The Painful External Costs of Bargaining - Evidence from a Railway Strike - Florian Timme (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Evidence is presented that the number of traffic deaths and traffic injuries increased significantly due to a railway strike in Germany. While the number of slightly and seriously injured people increased on all road types, the number of fatally injured people increased only on roads out of town. The data suggest that the timing of a strike plays a crucial role in the effect on traffic injuries. Effects are stronger on weekends (Friday to Sunday) than on weekdays.
Keywords: J45; J52; R41; 330